PENGUATAN EKSISTENSI BANGSA MELALUI SENI BELA DIRI TRADISIONAL PENCAK SILAT - Kumaidah, Endang (Faculty of Humanities, Diponegoro University, 2012)
National sport has a considerable influence in strengthening the existence of a nation. Pencak Silat is both a sport and a martial art originally Indonesian. More than just a means to protect self-defense, it can also be a vessel of nationalism, an identity of Indonesia in its art and aesthetic beauty. Its movements resemble those of Indonesian animals and uniquely contain traditional dance characteristic. In some ethnic cultures, this martial art becomes an integral part in rituals and religious ceremonies. It is then concluded that Pencak Silat may directly or indirectly build and develop the personality and noble character of Indonesian people through sportsmanship training. Keywords: Pencak Silat, nationalism, traditional martial art.